2022
DOI: 10.3390/s22124336
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Armeo®Spring Device to Assess the Effect of Trunk Stabilization Exercises on the Functional Capabilities of the Upper Limb—An Observational Study of Patients after Stroke

Abstract: Almost half of stroke patients report impaired function of the upper limb and hand. Stability of the trunk is required for the proper movement of the body, including the legs and arms. The aim of the study was to analyze the effect of trunk stabilization exercises on coordinated movement of the affected upper limb in patients after stroke, using an Armoe®Spring device and the “wall” and “abacus” functional tests. Materials and methods: This is a randomized, double-blinded study. The research was carried out in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…They suggested that progress in muscle strength with NDT may be due to activity training for normal movement or life activities during treatment sessions. Lee and Choi (2017) recommended trunk stabilization exercises for post-hospital stroke patients, while Olczak et al (2022) confirmed the necessity of NDT concept-recommended stabilization exercises for functional upper limb rehabilitation.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…They suggested that progress in muscle strength with NDT may be due to activity training for normal movement or life activities during treatment sessions. Lee and Choi (2017) recommended trunk stabilization exercises for post-hospital stroke patients, while Olczak et al (2022) confirmed the necessity of NDT concept-recommended stabilization exercises for functional upper limb rehabilitation.…”
Section: Discussionmentioning
confidence: 86%
“…Lee and Choi (2017) recommended trunk stabilization exercises for post‐hospital stroke patients, while Olczak et al. (2022) confirmed the necessity of NDT concept‐recommended stabilization exercises for functional upper limb rehabilitation.…”
Section: Discussionmentioning
confidence: 99%
“…According to the World Health Organization, physical rehabilitation is a set of interventions to optimise the body's functions and reduce the disability of people with various health problems [11]. Due to the awareness of the importance of functional and medical rehabilitation, rehabilitation services are continuously increasing, as well as chronic conditions and disabilities [10]. Medical rehabilitation aims to improve the quality of life, ensuring, in addition to the acquisition of functional independence, the individual's reintegration into society, one of the main objectives established at the beginning of a rehabilitation program [12].…”
Section: Medical Rehabilitation: New Therapeutic Approachesmentioning
confidence: 99%
“…IMUs are easy to incorporate, compatible with a variety of contexts, and present fewer privacy problems. This device seems to be a potential solution for monitoring adherence to rehabilitation protocols and posture [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Rehabilitation robots are emerging as a promising therapeutic tool for children and AYAs with loss of mobility and disability [17][18][19][20][21]. They help to restore function and mobility and can be classified by their mechanical structure, i.e., end effectors or exoskeletons [17].…”
Section: Introductionmentioning
confidence: 99%